The Relevance Of The Book On Marriage Schedules By The Mufti Of The Kingdom Of Kubu, West Kalimantan To Fikih Subjects At Madrasah Aliyah - Sita Alpiah; Erwin Mahrus; Sukino (IJGIE (International Journal of Graduate of Islamic Education), 2023)
The Book of Marriage Schedules is the great work of Mufti Ismail Mundu, a book full of knowledge, a book that talks about marriage. This article aims to explore and examine the contents of the book Jadual al-Nikāh and its relevance to the jurisprudence curriculum at Madrasah Aliyah. Writing with a qualitative approach, and a philological (History) approach, namely to obtain content information, the form of text presented by the author of the book, and bibliographic methods, with textual data analysis techniques for the Marriage Schedule book by condensing the data, presenting the data and drawing conclusions. This research resulted in an overview of the contents of the Marriage Schedule book on the one hand and the PAI curriculum, especially Mapel Fiqh on the other hand. This research concludes that the relationship between the discussion of marriage jurisprudence in the Marriage Schedule and the Jurisprudence Curriculum has quite high relevance. Thus, it is hoped that this book can be used as a reference as an additional learning resource in the fiqh learning process. Another function is that this book can be used as a learning medium in SKI learning using an Islamic history approach, as a learning medium in learning local content using a historical approach to the development of Islam in West Kalimantan based on local wisdom.